ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA FRAUD PADA BANK BTPN SYARIAH CABANG KOTA MALANG - Siti Hakimatun Nisak; Moh. Amin; M. Cholid Mawardi (Universitas Islam Malang, 2021)
This study aims to determine the factors of pressure, opportunity, rationalization, capability and technology that affect the occurrence of fraud at Bank BTPN Syariah, Malang City Branch and to determine the factors that most influence the occurrence of fraud in the Bank. BTPN Syariah Malang City Branch. The type of research in the preparation of this paper is research (explanatory research). The population in this study were employees of Bank BTPN Syariah Malang City Branch, with a total sample of 35 employees with data analysis techniques using multiple linear regression analysis. Based on the results of research and discussion that has been done, it can be concluded that 1) Opportunity pressure, rationalization, capability and technology affect fraud at Bank BTPN Syariah Malang City Branch 2) Rationalization has a dominant influence on fraud at Bank BTPN Syariah Malang City Branch.Keywords: opportunity pressure, rationalization, capability, technology and fraud